Network pharmacological analysis and in vitro testing of the rutin effects on triple-negative breast cancer - Chang Cheng; Jia Ruiying; Fang Bin; Miao Yaoyao; Zhang Lili (Open Medicine)
This study aims to assess the potential mechanism of rutin to treat triple-negative breast cancer (TNBC) based on network pharmacology followed by in vitro experiments.